f(x)=x^5+ax^3+bx-8 若f(-2)=10求f(2)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 02:30:49
f(x)=x^5+ax^3+bx-8若f(-2)=10求f(2)f(x)=x^5+ax^3+bx-8若f(-2)=10求f(2)f(x)=x^5+ax^3+bx-8若f(-2)=10求f(2)令g(x
f(x)=x^5+ax^3+bx-8 若f(-2)=10求f(2)
f(x)=x^5+ax^3+bx-8 若f(-2)=10求f(2)
f(x)=x^5+ax^3+bx-8 若f(-2)=10求f(2)
令g(x)=x^5+ax^3+bx
g(x)=-g(-x)所以g(x)是奇函数
f(x)=g(x)-8
f(-2)=g(-2)-8=10
g(-2)=18
f(2)=g(2)-8=-g(-2)-8=-18-8=-26
若f(x)=ax^3-bx+5且f(-2)=8,求f(2).
已知f(x)=x^5+ax^3+bx-8,若f(-2)=10,则f(2)=(
f(x)=x^5+ax^3+bx-8 若f(-2)=10求f(2)
若函数f(x)=x^5+ax^3+bx-8且f(2)=-26,求f(-2)
若f(X)=ax³-bx+5且f(-2)=8,求f(2)
若f(x)=ax^7+bx^3+cx+8,f(-5)=-15,则(5)=f(x)=ax^7+bx^3+cx+8f(-x)=-ax^7-bx^3-cx+8=-[ax^7+bx^3cx+8]+16=-f(x)+16f(x)=16-f(-x)f(-5)=-15所以f(5)=16-f(-5)=3116是怎么来的?
设f(x)=x^5+ax^3+bx-8,且f(-2)=10,则f(x)=
已知f(x)=x^5+ax^3+bx+8,且f(-2)=10,求f(x)
已知函数f(x)=ax^5+bx^3+cx+3,若f(5)=8,求f(-5)
已知f(x)=ax^2+bx+c,若f(-1)=f(3)=8,f(0)=5,求f(x).
f(x)=x^5+ax^3+bx-5 f(-2)=5 求f(2)
已知f(x)=x^5 + ax^3 + bx – 8 ,f(-3)=10 ,求f(3).
已知f(x)=x^5+ax^3+bx+8,且f(-2)=5,求f(2)的值.
已知f(x)=x^5+ax^3+bx-8,且f(-2)=10,则f(2)=什么
已知函数f(x)=x^5+ax^3+bx-8且f(-2)=10.则f(2)=
f(x)=x^5+ax^3+bx-8 ,f(-2)=10,那么f(2)=?
已知f(x)=x^5+ax^3+bx-8,且f(-2)=10,则f(2)等于多少
已知函数f(x)=x^5+ax^3+bx-8 qie f(-2)=10 那么f(2)等于